Thematic Progression on Third Grade Students‘ Writing in www.thewritesource.com - Lia Elyani Sukawatie (EDULANGUE, 2018)
This paper aims at describing the thematic progression which appears in the native 3rd grade students. This study examines the native students‘ writing, particularly their persuasive paragraph and narrative personal paragraph. The researcher took 2 texts out of 12 texts in www.thewritesource.com. The data analysis was grounded in the technique developed by Martin and Rother in Paltridge (2000:140). The result of this study showed that multiple theme patterns dominated the thematic progression development. The second one was reiteration theme, and the last was zig-zag pattern.